2023
DOI: 10.1097/md.0000000000033901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of patient support group on health literacy: a study using the Multidimensional Health Literacy Questionnaire

Abstract: Health literacy is important for patient care. Patient support group (PSG) is also crucial for patient education. Little is known about the effect of PSG on health literacy. We studied scores of health literacy before and after the intervention of a PSG. We also collected patient characteristics like age, gender, first-time participation or not, source of participants, and major diseases. We then identified factors associated with improved health literacy. A total of 43 participants (including patients and fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In individuals with breast cancer, those who joined a peer support group felt a sense of belonging and reduced levels of anxiety and reported overall increased scores in the mental aspect of the quality of life (Taleghani et al, 2012). Beyond the well-documented impact on the quality of life, there have been reports that showed that patient support groups can improve aspects of health literacy (Wu et al, 2023). As noted by Flowers et al, the low prevalence of GS contributes to limited knowledge about the disease.…”
mentioning
confidence: 99%
“…In individuals with breast cancer, those who joined a peer support group felt a sense of belonging and reduced levels of anxiety and reported overall increased scores in the mental aspect of the quality of life (Taleghani et al, 2012). Beyond the well-documented impact on the quality of life, there have been reports that showed that patient support groups can improve aspects of health literacy (Wu et al, 2023). As noted by Flowers et al, the low prevalence of GS contributes to limited knowledge about the disease.…”
mentioning
confidence: 99%